Recent trends in ultra-high performance concrete (UHPC): Current status, challenges, and future prospects. (17th October 2022) - Amran, Mugahed; Huang, Shan-Shan; Onaizi, Ali M.; Makul, Natt; Abdelgader, Hakim S.; Ozbakkaloglu, Togay
Highlights: UHPC is promptly developing as a leading concrete material for construction industries. UHPC has exceptional properties, making it a potential functional solution for a sustainable construction. This article scientifically reviews the carbon capturing, challenges, limitations, and applications of UHPC. The findings of this review likely to help specialists in establishing the design guidelines for sustainable UHPC. Further efforts are required to standardize testing characterization for the materials used in UHPC. Abstract: Ultra-high performance concrete (UHPC) combines advanced fibrous and cementitious material technologies to achieve high strength and exceptional durability. The material tends to have microscopic pores that prevent harmful substances such as water, gas, and chlorides from entering. UHPC can also achieve compressive strengths above 200 MPa and tensile strengths above 20 MPa. It also shows significant tensile strain hardening and softening behavior. Owing to all these characteristics, UHPC has excellent performance, making it a potentially attractive solution for improving the sustainability of construction components. Despite UHPC's outstanding mechanical properties, superior toughness and ductility, and extraordinary durability, various challenges prevent its widespread use. At the same time, several challenges are currently being faced in the applications of UHPC, which include i) design aspects such as material properties; ii) production technology for large-volume and/or long-span elements with low workability, high spalling, and high shrinkage strains; and iii) unknown durability characteristics after the appearance of long-term concrete cracking. With a lack of industry experience, UHPC specialists face additional challenges in spreading hands-on practice to concrete industry professionals so that the latter can be well versed in applying this sophisticated concrete technology. For these reasons, a comprehensive literature study on recent development trends of UHPC should be conducted to determine its current status and prospects. This article scientifically reviews the current status, carbon capturing capabilities, sustainability aspects, challenges and limitations, and potential applications of UHPC. This state-of-the-art review is aimed at helping scientific researchers, designers, and practitioners widen the use of UHPCs in advanced infrastructure applications. This review will help specialists to develop the design guidelines to enable the widespread application of sustainable UHPC. In doing so, design engineers will be provided with an assurance to fully exploit the high strength and other special properties of UHPC and develop models that can efficaciously estimate the ultimate bearing capacity of UHPC sections under various loading conditions.